A study of rare earth elements enriched carbonisation material prepared from Dicranopteris pedata biomass grown in mining area - Liujun Feng; Zhiqiang Chen; Haiyan Wang; Zhibiao Chen; Zuliang Chen; Jianhua Liu; Yuee Zeng (Scientific Reports)
Abstract Phytoremediation is currently a very popular remediation method for salvaging rare earth mining sites. However, there is still a challenge concerning how to use secondary resources such as plant biomass following the extraction of rare earth elements (REEs). Herein, Dicranopteris pedata (Houtt.) Nakaike, a REEs hyperaccumulator, served to fabricate REEs-rich carbonisation materials (REEs/C) at different temperatures. The results showed that the percentages of Pb(II) removed using REEs/C prepared at 400 °C (REEs/C-4) and 800 °C (REEs/C-8) were 85.1% and 84.0%, respectively. These amounts were better than that of REEs-C prepared at 600 °C (REEs/C-6 (67.0%)). Characterisation analysis confirmed that rich functional groups like aromatic, hydroxyl and C = C/C-C in REEs/C-4 provided more chelation sites to effectively complex with Pb(II), while the superior removal capacity of REEs/C-8 resulted from the enrichment of more REEs and abundant pore structure. Chemisorption, such as ion exchange and chelation, plays a significant role in adsorption. During the carbonisation process of REEs/C, the REEs enriched in Dicranopteris pedata contributed to the formation of rare earth oxides and oxygen vacancies in the material, and these properties enhanced the Pb removal ability of REEs/C. Moreover, the REEs contained in the material did not cause a leaching phenomenon during Pb removal, which is a safe and environmentally friendly material. Finally, the REEs/C was applied to wastewater, and it was found that this material could effectively adsorb Pb from wastewater. Overall, this study generates a new insight into: firstly, how to use phytoextracted biomass containing REEs as valuable REEs/C materials; and secondly, how to save the environment by using technology that promotes recycling of used materials.